Critical Analysis of Universal Issues in Healthcare and Beyond - Aldaghman, Adel Eidah Saeed; Doghman, Ibraheem Edah Saeed Al; Doghman, Ahmed Edah Saeed Al; Yami, Hamad Manssor Mohammed Al; Ghobari, Rahmah Mubarak Mabrook Al; Alsaad, Khmais Omran Khmais; Yami, Namah Saleh Abdulah Al; Alshareef, Hamad Saud Hamad; Alomar, Eetdal Mubarak Saleh; Almabkhoot, Salha Naser Said (Journal of Ecohumanism, 2024)
The healthcare system should aim to offer all accessible, equitable, and optimal medical care to clients, in return is confronted with a plethora of common global threats that hinder the offer of healthcare by affecting the healthcare system's access, equity, and quality. This paper provides an exploration of prominent topics in global health systems, including demand disparities, the influence of pandemics, resource distribution, and policy/health system problems. This paper will review the literature, analyze the problems, and then outline recommendations for these issues. By examining these global concerns, the study seeks to facilitate improvements in existing healthcare practices, government policies, and technology development to improve the future, providing approaches to meet needs effectively.